In silico discovery of potential azole-containing mPGES-1 inhibitors by virtual screening, pharmacophore modeling and molecular dynamics simulations - KÜÇÜKGÜZEL, İLKAY; OGAN, AYŞE (My University, 2022)
Inhibition of microsomal prostaglandin E-2 synthase-1 (mPGES-1) is promising for designing novel nonsteroidal anti-inflammatory drugs, as they lack side-effects associated with inhibition of cyclooxygenase enzymes. Azole compounds are nitrogen-containing heterocycles and have a wide use in medicine and are considered as promising compounds in medicinal chemistry. Various computer-aided drug design strategies are incorporated in this study. Structure-based virtual screening was performed employing various docking programs. Receiver operator characteristic (ROC) curves were used to evaluate the selectivity of each program. Furthermore, scoring power of Autodock4 and Autodock Vina was assessed by Pearson\"s correlation coefficients. Pharmacophore models were generated and Guner-Henry score of the best model was calculated as 0.89. Binding modes of the final 10 azole compounds were analyzed and further investigation of the best binding (- 8.38 kcal/mol) compound was performed using molecular dynamics simulation, revealing that furazan1224 (ZINC001142847306) occupied the binding site of the substrate, prostaglandin H-2 (PGH(2)) and remained stable for 100 ns. Continuous hydrogen bonds and hydrophobic interactions with amino acids in the active site supported the stability of furazan1224 throughout the trajectory. Pharmacokinetic profile showed that furazan1224 lacks the risks of inhibiting cytochrome P450 3A4 enzyme and central nervous system-related side-effects.
Keywords: Kimya; Biyokimya; Alkoloidler; Fizikokimya; Sıvı Kristaller ve Sıvı Kristal Polimerler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Physical Chemistry; Liquid Crystals and LCP; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); KİMYA, FİZİKSEL; KRİSTALLOGRAFİ; CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, PHYSICAL; CRYSTALLOGRAPHY; Surfaces and Interfaces; Chemistry (miscellaneous); General Chemistry; Physical and Theoretical Chemistry; Surfaces, Coatings and Films; Physical Sciences; mPGES-1; Anti-inflammatory drug; Virtual screening; Pharmacophore modeling; Molecular dynamics; DRUG DISCOVERY; DOCKING; DATABASE; INSIGHT